2004
DOI: 10.1197/jamia.m1535
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Digital Divide: Reaching Vulnerable Populations

Abstract: The AMIA 2003 Spring Congress entitled "Bridging the Digital Divide: Informatics and Vulnerable Populations" convened 178 experts including medical informaticians, health care professionals, government leaders, policy makers, researchers, health care industry leaders, consumer advocates, and others specializing in health care provision to underserved populations. The primary objective of this working congress was to develop a framework for a national agenda in information and communication technology to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
171
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(181 citation statements)
references
References 12 publications
3
171
1
6
Order By: Relevance
“…The digital divide threatens to further harm the health of these vulnerable populations by excluding them from the benefits of internetbased communication with their health care provider. [20][21][22] Understanding and advancing the use of health information technology among vulnerable populations has therefore been identified as a national research and policy priority. 12,13 Moreover, there is evidence of a 'digital divide' in the U.S., particularly an inequity in internet access for those with fewer economic and social resources.…”
Section: Introductionmentioning
confidence: 99%
“…The digital divide threatens to further harm the health of these vulnerable populations by excluding them from the benefits of internetbased communication with their health care provider. [20][21][22] Understanding and advancing the use of health information technology among vulnerable populations has therefore been identified as a national research and policy priority. 12,13 Moreover, there is evidence of a 'digital divide' in the U.S., particularly an inequity in internet access for those with fewer economic and social resources.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Vulnerable groups such as African-Americans or those with low socioeconomic status are less likely to use EMRs or patient portals, [9][10][11][12][13][14][15][16] in part because they are less likely to use the Internet at all. [17][18][19][20] Health literacy may also play an important role in determining whether elderly patients are willing and able to use EMRs and other Internet-based health tools. Surprisingly, given the substantial body of research that documents the importance of health literacy in health behaviors and outcomes, [21][22][23] it has been largely overlooked as a determinant of health IT use.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, although studies, such as Chang et al [19], reported patients' individual characteristics can interact with technology to contribute to vulnerability, which potentially influence their technology usage behavior, no study to date investigated the influence of individual characteristics such as personality traits on individuals' patient portal usage behavior. In addition, although the importance of health emotion in technology adoption behavior emerged in recent years [22,23], the impact of this factor on patient portal use is still unexplored and remained unknown.…”
Section: Health Status Emotion In Healthcarementioning
confidence: 99%
“…A review of technology adoption literature [15][16][17][18] suggests that individuals' personality traits are also important in influencing technology adoption behavior. Chang et al [19] stated that patients' individual characteristics can interact with technology, which potentially influence their technology usage behavior. Dispositional factors, such as individuals' personality traits, that are mostly counted in Education, Organizational Behavior, and Human Psychology disciplines are left largely unexplored in Information Technology (IT) literature [20].…”
Section: Introductionmentioning
confidence: 99%